The Hermeneutics of Conversion: Apostrophe, Reader Engagement, and the Medusa-Beatrice Binary - Kelly, Deana Basile (Quaderni d'Italianistica)

(untitled) (Iter Press, 2022)
This essay traces the parallels between Vita nuova 19 and the impasse at the gate of the City of Dis in Inferno in order to propose Medusa and Beatrice as diametrically opposed figures. Whereas Beatrice activates the intellect and catalyzes internal reflection and conversion, Medusa deactivates the intellect and obstructs reflection and conversion. Moreover, contextualizing the Medusa figure within the wider approach to the gate in Inferno 8 and 9 reveals the figure to be linked to the forging of the poet’s novel apostrophic mode of reader engagement inaugurated in those cantos. Dante weaves into both of these episodes a philosophical / theological discourse of light and darkness, drawing upon Aristotelian sources filtered through Guido Guinizzelli, as well as the Pauline dialectic of light and darkness in 2 Corinthians. Moreover, Dante the poet unfolds the Medusa / Beatrice binary alongside his development of his novel apostrophic mode, thus laying out the parallel actions of viewer and reader, both of which depend upon healthy intellects capable of absorbing and reflecting divine light in a way that brings about conversion.